Determination of energy damping upon impact load in reinforced concrete sandwich plates with different core geometries - Savas, S.; Ulker, M.; Turgut, S.; Bakir, D. (Sharif Univ Technology, 2021)
It can be challenging to analyze Reinforced Concrete (RC) sandwich plates with hollow structures under impact loads in terms of crushing, punching, cracking, and crack trajectories via static and dynamic equations. In the literature, the finite element solutions were provided after determining the behaviors of the materials based on the test results. Therefore, it is required to test the behaviors of RC plates. To this end, the behaviors of sandwich plates under impact loads were experimentally analyzed in this study. The sandwich plates were manufactured by cutting Polyester Foams (PF) into hexagonal prisms, square prisms, I-type, and S-type and installing them inside the RC plates. The manufactured sandwich plates were 27% lighter than full plates. A weight of 320 kg declined freely from 2.5 in, and the load was implemented at the center of the plate at a velocity of 7.5 m/s. Similar implementations were also conducted for filled plates and the maximum displacements were measured in both types of plate tests. The measurements obtained from each test were compared to determine the sandwich plate with the core geometry which provided the highest absorption and the lowest displacement. In the analyses, the S-type core geometry exhibited greater absorption than other core geometries. (C) 2021 Sharif University of Technology. All rights reserved.
Keywords: Sandwich plate; Impact load; Impact test; Impact effect; Reinforced concrete